2022
DOI: 10.3390/logistics6010015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blockchain Technology in Manufacturing Supply Chain and Logistics

Abstract: Background: Blockchain is a digitally managed, distributed, and decentralized ledger used to record transactions in an immutable format. Its characteristics in providing trust, transparency, and traceability make it attractive for applications where transactions are involved. Originally intended to support financial transactions, the technology has gained attention even in non-financial sectors such as health care, manufacturing, retail, and government services. Methods: For centuries, the various functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(63 citation statements)
references
References 55 publications
(49 reference statements)
0
63
0
Order By: Relevance
“…It has high efficiency in information transmission because it comprises countless blocks with block headers, data blocks, and block bodies. The block header includes hash values, time tags, random digital tags, and other information [ 23 ]. The data block stores the data to be transmitted.…”
Section: Blockchain Technologymentioning
confidence: 99%
“…It has high efficiency in information transmission because it comprises countless blocks with block headers, data blocks, and block bodies. The block header includes hash values, time tags, random digital tags, and other information [ 23 ]. The data block stores the data to be transmitted.…”
Section: Blockchain Technologymentioning
confidence: 99%
“…Furthermore, the role of blockchain in fostering renewable energy technologies, circular economy, as well as electric mobility, and charging will remain an important area of future research in the blockchain and energy fields [84]. Lastly, as blockchain is expected to revolutionize supply chains, future research should examine its impact on global and local energy supply chains and the concept of sustainable supply chain management [18,19,39,43,[52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…It also helps to verify the provenance of a product and related sustainability practices, that is, if there are any fraudulent and unethical labor practices involved [98]. In manufacturing processes, blockchains can be utilized for spare parts tracking and monitoring of the current equipment, but also for shipping automation, which has the major potential to provide more time efficiency and reduce operational and repairing costs [44,61,62].…”
Section: Contribution To the Circular Economymentioning
confidence: 99%
“…By assessing, arranging, and summarizing the literature, the authors of [ 35 ] offered a comprehensive overview of blockchain technology’s role in tackling supply chain and logistics-related concerns. The proposed study demonstrated that blockchain technology may transform the supply chain and logistics services into secure, flexible, trustworthy, and transparent operations.…”
Section: Related Surveysmentioning
confidence: 99%